Sphaerodoridium Lutzen 1961 ... - Moreira, Juan; Parapar, Julio (Zenodo, 2015)
Genus Sphaerodoridium Lützen, 1961 emended by Fauchald, 1974 Type species. Sphaerodoridium claparedii (Greeff, 1866). ... : Published as part of Moreira, Juan & Parapar, Julio, 2015, A new species of Sphaerodoridium Lützen, 1961 from Iceland (Polychaeta: Sphaerodoridae), pp. 91-105 in Zootaxa 3911 (1) on page 93, DOI: 10.11646/zootaxa.3911.1.5, http://zenodo.org/record/236683 ...